PENGARUH PROTIFABILITAS, FREE CASH FLOW, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN - Robert Jao; Ana Mardiana; Anthony Holly; Ervina Nelvani Depthios (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This purpose of this study was to investigate the effect of profitability, free cash flow, capital structure on increasing firm value through dividend policy. This study was built with signalling theory and bird in hand theory. The population used in this study were manufactur companies listed on Indonesia Stcok Exchange (IDX) on the period of 2020-2022. This study uses secondary data which is annual report that published by IDX and company official website. The sample selection in this study used purposive sampling method, in order to obtain a total sample of 48 companies. The data analysis technique used is path analysis. The result of this study shows that profitability has a positive and not significant effect on dividend policy. Free cash flow has a positive and significant effect on dividen policy. Capital structure has a negative and significant effect on dividen policy. Profitability, free cash flow, and dividend policy have a positive and significant effect on firm value. The result of this study also shows that dividend policy isn’t able to mediate the effect of profitability on firm value. Dividend policy is able to mediate the effect of free cash flow and capital structure on firm value.